A history of disinformation in the U.S. - Hayden, Joseph R., author.
1 online resource (xii, 336 pages).
Keywords: "This volume recounts notable episodes of distortion throughout American history. It examines several of the lurid hoaxes and conspiracy theories that have inspired press coverage, as well as some of the political lies promoted by partisan gladiators, whether of the eighteenth century or today. The book moves beyond the sensational stories to show the enduring and systemic nature of media manipulation that occurs on far more consequential issues. It exposes persistent and deeply destructive falsehoods that have been told about women, people of color, immigrants, the LGBTQ+ community, unions, commercial products and enterprises, drugs and drug users, highlighting how longstanding "bipartisan" myths have effectively marginalized certain groups of Americans. Alongside these cases, the author carefully dissects the changing nature of institutions, technologies, and practices of journalism in America. Attention is given to the evolution of newspapers in the eighteenth and nineteenth centuries, the role of broadcasting in the twentieth, and the impact of the internet and social media at the dawn of the twenty-first. This book will appeal to readers interested in American history, journalism, communication studies, political science and sociology"--